FOAMTASTIC: FOAM PEMBERSIH SEPATU INSTAN TANPA BILAS BERBASIS LIMBAH SABUT KELAPA DAN KULIT JERUK SUNKIST SEBAGAI ALTERNATIF MENGURANGI LIMBAH: Foamtastic: Instant Rinseless Shoe Cleaning Foam Based on Coconut Fiber and Orange Peel Waste as an Alternative to Reduce Waste - Komalasari, Siti; Yulianti, Wina; Hakim, Diana Faoziah; Tanwiroh; Pangastuti, Tiasuri (IPB University, 2024)
Busy activities and high rainfall can quickly get shoes dirty, so an instant and rinse-free shoe cleaner is needed. This instant shoe-cleaning innovation without rinsing can utilize sunkist coconut fiber and orange peel waste, which are abundant. The coconut husk waste is processed into ash, and its potassium content is extracted as a polish and alkaline source. The sunkist orange peel undergoes citric acid extraction using the maceration method, which can potentially be an antibacterial agent. Five formulations of foamtastic are made with various compositions. Each formulation is tested for cleaning power against various stains, antibacterial properties, foam height, and stability. Formulation 4 is the best formulation based on optimal cleaning power, antibacterial properties, foam stability, and safe and effective pH for use as a cleaning product. Keywords: Formulation, Sunkist orange peel, shoe cleaner, coconut fiber